Self-Medication among Pregnant Women in Effutu and Agona West Municipalities of the Central Region of Ghana - Jacqueline Nkrumah; Fred Yao Gbagbo (Journal of Public Health International, 2019)
Self-medication in pregnancy is a health concern in Ghana. We assessed the practice among 136 pregnant women in Effutu and Agona West Municipalities using facility-based, cross-sectional design and mixed method approach of data collection. Data analysis used SPSS and manual content analysis. Results show that pregnant women of all backgrounds self-medicate, with prevalence of 69%, motivated by cheaper treatment cost (17%), minor ailments (29%) and positive outcomes (33%). Commonly used medications include antibiotics (23%), pain killers (20%) and herbal preparations (19%). Preventing self-medication in pregnancy therefore requires awareness creation and evidence based Social Behavioral Change Communication on associated dangers.
Keywords: Self-Medication